HUBUNGAN STATUS GIZI DENGAN PENINGKATAN FUNGSI KOGNITIF ANAK USIA 7-9 TAHUN DI DESA PALLIMAE KECAMATAN SABBANGPARU KABUPATEN WAJO - Hasnidar, Hasnidar (FORUM ILMIAH KESEHATAN, 2022)
Children who have decreased cognitive function are characterized by decreased learning achievement. This could be due to the lack of fulfillment of nutrition provided by parents. The purpose of this study was to determine the relationship between nutritional status and increasing cognitive function of children aged 7-9 years in the working area of the Liu Health Center (Pallimae Village). The research design was cross-sectional. The research subjects were 74 children aged 7-9 years who were selected through purposive sampling method. The data collection instrument was a questionnaire regarding nutritional status and cognitive function improvement. Data were analyzed using Chi square test. The results showed that children aged 7-9 years in the category of fulfilled nutritional status = 39 (52.7%), nutritional status was not fulfilled = 35 (47.2%), while the increase in cognitive function was good = 45 (60.8%) and increase in cognitive function is not good = 29 (39,1%). The results of the hypothesis test showed p = 0.000. Furthermore, it was concluded that there was a significant relationship between nutritional status and increased cognitive function. It is expected that parents maintain their children's diet so that their cognitive function increases.Keywords: child; nutritional status; cognitive function ABSTRAK Anak yang mengalami penurunan fungsi kognitif ditandai dengan prestasi belajar yang menurun. Hal ini bisa disebabkan karena kurangnya pemenuhan gizi yang diberikan oleh orang tua. Tujuan penelitian ini adalah untuk mengetahui hubungan antra status gizi dengan peningkatan fungsi kognitif anak usia 7-9 tahun di wilayah kerja Puskesmas Liu (Desa Pallimae). Rancangan penelitian ini adalah cross-sectional. Subyek penelitian adalah 74 anak berusia 7-9 tahun yang dipilih melalui metode purposive sampling. Instrumen pengumpulan data adalah kuesioner mengenai status gizi dan peningkatan fungsi kognitif. Data dianalisis menggunakan uji Chi square. Hasil penelitian menunjukkan anak usia 7-9 tahun dalam kategori status gizi terpenuhi = 39 (52,7%), status gizi tidak terpenuhi = 35 (47,2%), sedangkan peningkatan fungsi kognitif baik = 45 (60,8%) dan peningkatan fungsi kognitif kurang baik = 29 (39,1%). Hasil uji hipotesis menunjukkan p = 0,000. Selanjutnya disimpulkan bahwa ada hubungan yang signifikan antara status gizi dengan peningkatan fungsi kognitif. Diharapkan orang tua menjaga pola makan anak agar fungsi kognitifnya mengalami peningkatan.Kata kunci: anak; status gizi; fungsi kognitif